2006
DOI: 10.1093/humrep/del159
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor modulator CDB-2914 down-regulates vascular endothelial growth factor, adrenomedullin and their receptors and modulates progesterone receptor content in cultured human uterine leiomyoma cells

Abstract: These results suggest that CDB-2914 down-regulates VEGF, ADM and their receptor contents and modulates PR isoform contents in cultured leiomyoma cells in a cell-type-specific manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 36 publications
1
61
1
4
Order By: Relevance
“…It was demonstrated that VEGF is necessary for the growth of leiomyoma xenografts in vivo (104). VEGF represents a potential therapeutic target in leiomyoma, and Xu and colleagues demonstrated that it is downregulated by the selective progesterone receptor modulator CDB-2914 (105).…”
Section: Role Of Individual Growth Factors In Leiomyoma Pathobiologymentioning
confidence: 99%
“…It was demonstrated that VEGF is necessary for the growth of leiomyoma xenografts in vivo (104). VEGF represents a potential therapeutic target in leiomyoma, and Xu and colleagues demonstrated that it is downregulated by the selective progesterone receptor modulator CDB-2914 (105).…”
Section: Role Of Individual Growth Factors In Leiomyoma Pathobiologymentioning
confidence: 99%
“…This action of VA 2914 was not observed in the surrounding normal myometrial cells, suggesting a cell type specific action of this SPRM on leiomyoma cells [68].…”
Section: Treatment Of Uterine Leiomyomatamentioning
confidence: 82%
“…Although it is structurally similar to mifepristone, ulipristal has less antiglucocorticoid activity providing a potential advantage for long term use. Unlike RU 486 which affected both leiomyoma and myometrial cells, UPA and asoprisnil affected only leiomyomata growth along with expression of growth factors, cytokines and proteases like MMP along with downregulating Bcl2 and upregulating caspase [37][38][39] . Levens et al evaluated the effect of 10 mg and 20 mg, CDB2914 administered 3 months in women with symptomatic fibroids in a randomized placebo controlled trials.…”
Section: Role Of Ulipristal Acetatementioning
confidence: 93%